2010
DOI: 10.1100/tsw.2010.124
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antitubercular Activity of Heteroaromatic Isonicotinoyl and 7-Chloro-4-Quinolinyl Hydrazone Derivatives

Abstract: Two series of N’(E)-heteroaromatic-isonicotinohydrazide derivatives (3a-f and 4a-b) and 1-(7-chloroquinolin-4-yl)-2-[(heteroaromatic)methylene]hydrazone derivatives (5a-f and 6a-b) have been synthesized and evaluated for their in vitro antibacterial activity against Mycobacterium tuberculosis H37Rv. Several compounds were noncytotoxic and exhibited significant minimum inhibitory concentration (MIC) activity (3.12, 2.50, 1.25, or 0.60 μg/mL), which can be compared to that of the first-line drugs ethambutol (3.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…In general, for Series 1 (Table 1), it was observed that the presence of substituents attached to the benzene ring which are electron withdrawing groups (EWG) by polar and by resonance effects, such as nitro (9 and 10) and cyano (11), seem to be less important to the biological activity than the presence of substituents which are EWG by polar effect but are electron donating groups (EDG) through resonance, such as halogens (2-4), hydroxyl (5 and 6), and methoxyl groups (7 and 8). Regarding this type of substituents, it was observed that when they are at the R 2 position (3, 4 and 8), the spectrum of antileishmanial activity is broader, except for the hydroxyl group (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, for Series 1 (Table 1), it was observed that the presence of substituents attached to the benzene ring which are electron withdrawing groups (EWG) by polar and by resonance effects, such as nitro (9 and 10) and cyano (11), seem to be less important to the biological activity than the presence of substituents which are EWG by polar effect but are electron donating groups (EDG) through resonance, such as halogens (2-4), hydroxyl (5 and 6), and methoxyl groups (7 and 8). Regarding this type of substituents, it was observed that when they are at the R 2 position (3, 4 and 8), the spectrum of antileishmanial activity is broader, except for the hydroxyl group (6).…”
Section: Resultsmentioning
confidence: 99%
“…All 7-chloro-4-quinolinyl hydrazone derivatives described in this work (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were previously synthesized by our research group. They were fully characterized by spectroscopic and spectrometric methods (10,11).…”
Section: Synthesismentioning
confidence: 99%
“…For series A , B , and C , the biological activity responses (i.e., minimum inhibitory concentration, MIC) were collected from the literature, [10,11,12] and for series D , from the current work (Table 1). The MIC (μM) values were expressed in negative logarithmic scale, i.e., pMIC (–LogMIC).…”
Section: Methodsmentioning
confidence: 99%
“…This kind of hydrazones and their metal complexes exhibit a variety of biological and pharmaceutical activities, being recognized as antimicrobial, antituberculosis, antitumoral and antioxidant agents [11][12][13]. Cytotoxicity assays of some organotin(IV) complexes containing INHOVA in a series of human cancer cell lines placed them as promising anticancer agents [14].…”
Section: Scheme 1 Inhovamentioning
confidence: 99%